2017
DOI: 10.1038/srep44990
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan induces Toll-like receptor 4-regulated reactive oxygen species and promotes endoplasmic reticulum stress-mediated apoptosis in lung cancer

Abstract: Fucoidan, a sulfated polysaccharide extracted from brown algae, exhibits anti-cancer activity. However, the effects and mechanism of fucoidan-induced apoptosis via endoplasmic reticulum (ER) stress is unclear. In this study, we demonstrated that fucoidan prevents tumorigenesis and reduces tumor size in LLC1-xenograft male C57BL/6 mice. Fucoidan induces an ER stress response by activating the PERK-ATF4-CHOP pathway, resulting in apoptotic cell death in vitro and in vivo. Furthermore, ATF4 knockdown abolishes fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 49 publications
1
55
0
1
Order By: Relevance
“…58,59) Accumulation of ROS production will directly damage mitochondrial coupling with dysfunction of ER. In the present study, bavachin not only activated ER stress but also disrupted mitochondrial function evidenced by depletion of MMP and increased ROS.…”
Section: Discussionmentioning
confidence: 99%
“…58,59) Accumulation of ROS production will directly damage mitochondrial coupling with dysfunction of ER. In the present study, bavachin not only activated ER stress but also disrupted mitochondrial function evidenced by depletion of MMP and increased ROS.…”
Section: Discussionmentioning
confidence: 99%
“…To alleviate this stress, autophagy can be triggered as a secondary response [71]. Recently, Hsu et al [72] showed that both commercial fucoidans from Laminaria japonica and F. vesiculosus prevented lung cancer cells via ROS-mediated induction, Chen et al [73] reported that commercial fucoidan from F. vesiculosus inhibited MDA-MB-231 breast cancer cells and HCT116 colon cancer cells by increasing the expression of CHOP (related to ER-stress), and Park et al [74] reported that AGS human gastric adenocarcinoma cells had enhanced autophagy and mitochondrial damage after treatment with commercial fucoidan (undefined source).…”
Section: F Vesiculosus Fucoidan Causes Stress-induced Apoptosis-likementioning
confidence: 99%
“…(−) indicates a negative control using transfection‐free HEK293T cells. Arrows indicate the Bip band, and arrowheads indicate unknown bands that were often detected when using the anti‐Bip antibody (Hsu et al ). (b) Quantification of co‐IP efficiency shown in (a).…”
Section: Resultsmentioning
confidence: 99%